ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PADA MATERI PYTHAGORAS BERDASARKAN TEORI KASTOLAN DI SMP NEGERI 2 LANGOWAN - Banne, Rahmat Saleh R. R. L; Pulukadang, Rosiah J.; Regar, Vivian E. (LPPM Politeknik Saint Paul Sorong, 2024)
The purpose of this study was to describe the errors made by students in solving story problems on pythagorean material in class VIII B SMP Negeri 2 Langowan based on Kastolan's theory. This research uses qualitative research, with the methods used in data collection are written tests in the form of description questions (essay), interviews, and documentation. The subjects in this study were class VIII Byang students totalling 29 students. Based on the results of the data obtained, it shows that in solving story problems on pythagorean material, students make mistakes at the stage of understanding the concept with a percentage of 15.17%, the stage of understanding the procedure with a percentage of 42% and the stage of understanding the technique with a percentage of 62%.